Analisis Vegetasi di Kawasan Karst Provinsi Gorontalo - Ali, Fathur Rahman M.; Katili, Abubakar Sidik; Husain, Ilyas H.; Utina, Ramli; Kandowangko, Novri Y.; Hamidun, Marini Susanti (CV. ULIL ALBAB CORP, 2025)
This study aims to determine the composition of vegetation types in the karst area of Gorontalo province and determine the vegetation structure in the karst area of Gorontalo province. The method used in this study uses the square transect method, the transect line is made perpendicular along 100 m, with the plot size being 20 x 20 m for tree strata, 10 x 10 m for pile strata, and 5 x 5 m for seedling strata, The results of vegetation structure analysis based on the highest INP value for tree-level strata at station I are Leucaena leucocephala species 2.20%, at Ceiba petandra station II 1.24%, and at Muntingia calabura station III 1.72%. At the stake level, the Leucaena leucocephala species had the highest INP value of the three stations, which was 1.81%. For the nursery rate, the highest INP is owned by the Leucaena leucocephala species at 2.10%. Based on the results of the analysis using ordinance charts, stations II and III have almost the same formation pattern so that the graph tends to overlap, while for station I it is very different from stations II and III, for station I it has its own formation pattern compared to stations II and III, and station I is also indicated to have its own characteristics based on habitat conditions and environmental factors.